Attractiveness of essential oils of three Cymbopogon species to Tribolium castaneum (Herbst) adults - Đukić, Nikola; Radonjić, Anđa; Andrić, Goran; Kljajić, Petar; Drobac, Milica; Omar, Eihab; Kovačević, Nada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Behavior bioassays were conducted in the laboratory (23 ± 1ºC and 50 ± 5% r.h.) usingthe olfactometer to determine the effects of essential oils of three plant species in theCymbopogon genus (Lemongrass), Cymbopogon nervatus, C. proximus and C. schoenanthus, on adults of Tribolium castaneum. The effect of essential oils was compared to a commercial biopesticide based on azadirachtin at three concentrations (0.0001, 0.001 and 0.01%).The results showed that all essential oils and the azadirachtin-based biopesticide had significant (p
Keywords: Essential oils; Cymbopogon; Red flour beetle; Behaviour; Repellency